Como ser um bom professor características de professores efetivos e professores modelos pela perspectiva de alunos de medicina - Carvalho, Diogo Couto de (2022)
Introduction: The teacher's role in education-learning process has changed over the years. Several types of teachers have already been described and their relationship with the teaching- learning process is a constant target of research. Effective teachers are those who help the student to achieve a goal. Positive role models teachers are those who inspire students to be like them, professionally or even personally. Negative role models are those who encourage repulse in students about bad behaviors or attitudes. The present study sought to understand the characteristics of effective teachers, positive and negative role models, by undergraduate medical students. Methodology: The present work was a qualitative study that sought to understand the characteristics of effective teachers, positive and negative role models, by undergraduate medical students. Data were collected through semi-structured interviews and a thematic content analysis was performed. Results and discussion: 19 interviews were collected, 9 with second-year students and 10 with fourth-year students. In terms of effective teachers, second-year students valued more empathic aspects instead of cognitive skills. Fourth-year students, in turn, valued more cognitive and interpersonal skills. About positive role models, second-year students highlighted more empathic characteristics with themselves, effective communication skills and moderately authoritarian attitudes in the teaching environment. On the other hand, fourth-year students emphasized empathic characteristics in relation to the patient, interpersonal skills, and recognition of knowledge limits by the teacher. As for the perception of negative role models, second-year and fourth-year students showed similar views, but second-year student’s shows more interest in empathic characteristics, with a focus on the student, while fourth year students valued more the empathy presented with the patient. Conclusion: Second and fourth-year medical undergraduate students identify characteristics associated with effective teachers, positive and negative role models, and these characteristics are different in several aspects between the years analyzed. The individualized training of teachers with a focus on the year in which they will work can generate better educational outcomes, both in terms of teachereffectiveness and in acting as role model.